Morthometric radiation–anatomy of brain structures with its volumetric formations of the cerebral and extra-cerebral location (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In recent years, surgery, neurology, forensic medicine (and other clinical specialties) are increasingly developing as age-specific sciences, with the desire to strictly take into account the anatomical and physiological features of age, to differentiate the appropriate methods of diagnosis and treatment. It is known that not only the size, shape, and position of organs change with age, but also their internal design. Therefore, to study the structure and topography of organs regardless of certain age periods means to admit the clear possibility of erroneous medical conclusions. The most acute lack of data on age-related anatomy is felt when working with elderly and senile patients. Stable size and weight indicators of organs and their constituent parts are characteristic of mature age, so morphometric indicators of organs and individual body parts of this age period are the starting points (reference points) that allow not only to objectively see and correctly assess the severity of changes in postnatal ontogenesis, but also to analyze the dynamics of age-related structural transformations.